SenseWeb: Browsing the Physical World in Real Time (Demo Abstract) - Santanche, Andre; Nath, Suman; Liu, Jie; Priyantha, Bodhi; Zhao, Feng (IPSN'06: ACM/IEEE Information Processing in Sensor Networks, 2006)
Geo-centric web interface such as MSN Virtual Earth (http://local.live.com) and Google Maps (http://maps.google.com) are useful to visualize spatially and geographically related data such as addresses, neighborhoods, weather, traffic, and so on. Desires to augment additional useful information to these interfaces have led people to create custom applications that overlay their own data on top of browsable maps. Examples of such applications overlay housing information (http://www.housingmaps.com) and crime-rate data (http://www.chicagocrime.org/map/) on Google maps, locations of vehicles (http://jprestonsystems.2mydns.com/ vemap.aspx?name=demoacct2) and podcasters (http://www.podlook.com/map.aspx) on MSN Virtual Earth, weather data on custom maps (http://www.wunderground.com), etc. Such applications have been possible after Google Maps and MSN Virtual Earth have published useful APIs to overlay location data on their maps.